Uji Ekstrak Bawang Putih Tunggal (Allium sativum L.) Terhadap Bakteriuria Escherichia coli Pada Calon Pekerja Migran Indonesia - Indah Sulistiyawati; Muhammad Falah; Ari Dwi Nurasih (Biotropic : The Journal of Tropical Biology, 2021)
Garlic (Allium sativum L) is a tested type of phytopharmaca because it is proven to have beneficial benefits as antibacterial and protect the body from pathogens. The majority of Indonesian Migrant Workers, especially Prospective Indonesian Migrant Workers (CPMI), are indicated to be susceptible to Urinary Tract Infection (UTI), which is caused by the bacteriuria Escherichia coli. In this study, the crude extract of single garlic (A. sativum L) will be used as an antibacterial against E. coli bateriuria in the urine sample of CPMI, with variations in the concentration of single crude extract of garlic, namely; 0%, 25%, 50%, 75%, and 100%. This research was conducted in a period of 1 (one) year from January to December 2020, with urine research samples from CPMI in the Banyumas Regency area. Extraction was carried out by extracting a single garlic using 96% ethanol solvent in a ratio of 1: 1, then evaporated to produce a filtrate that would be tested with a varied concentrate composition. Isolation of bacteriuria in urine samples using EMBA selective media. From a total of 37 urine samples, 17 about 46% were positive for E. coli, and 20 samples were 54% negative for E. coli. Bacteriuria that was found challenged with crude garlic extract resulted in differences in the antibacterial test at several extract concentrations with amoxicillin positive control, with One Way Anova a P-value = 0.000 <0.05, and continued with the analysis of the Post Hoc Test and the Tuckey Test, that the garlic extract The single most effective used as an anti-bacterial agent is the concentration of 100%, resulting in an average inhibition of 12.81 mm. The ability of single garlic extract to inhibit increases with increasing extract concentrate.